Korban Penghilangan Paksa pada Konflik Aceh; Upaya Pemulihan dan Pemenuhan Hak Korban Melalui Mekanisme KKR Aceh - Muhammad Yunus (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
Conflict victims are important entities in maintaining peace. However, after 16 years of peace in Aceh, there are still many victims and families of conflict victims who have not fully received attention, especially the families of victims of enforced disappearances during the Aceh conflict. Indeed, they need certainty about the whereabouts or status of their missing family members. This study examines the status of victims of enforced disappearances during the Aceh conflict and what rights of victims or victims' heirs can be resolved through the mechanism of the Truth and Reconciliation Commission. This research uses the perspective of history, law and human rights. The data used come from various sources. The data are then analysed, narrated and described qualitatively. The results of the study indicate that there are several steps that can be taken to carry out the rights of victims and families of victims of enforced disappearances, namely through a court decision process, in the context of Aceh carried out by the Mahkamah Syar'iyah. Courts need to establish legal status for victims as a form of recognition that enforced disappearances occurred during the conflict. After obtaining legal certainty, the next step is to accomplish the right of reparation through the Commission of Truth and Reconciliation. Then, followed by granting residence status; provision of missing person certificate; compensation for deceased victims; memorialization of victims; and excavation of mass graves.